Analysis of relationship between trade costs and Uzbekistan`s bilateral trade: theories and concepts - Shomurodov Tokhir Boymurod ugli; Karimova Latofat Sadullayevna; Ganiev Bakhtiyor Zulfikor ugli; Quziyeva Gulnoza Rashidovna; Rahmonov Bekzod Sharibjon ugli (Research Parks Publishers, 2021)
This paper examines the factors affecting Uzbekistan's bilateral trade flows, especially the relationship between trade costs and trade volume over the past decade. It uses a variety of tests, a gravity model, and an OLS regression method. The obtained results are similar to the previous literature, but some unexpected results were observed. It also provides conclusions and recommendations for future problems through the analysis of the results obtained. The main independent variable trade cost showed its expected result. A percentage increase in trade costs will reduce Uzbekistan's bilateral trade volume by 0.03%. Its relationship with bilateral trade is negative and significant